Estrogen receptor α expression in different stages of salivary gland mucoepidermoid carcinoma - Forooz Keshani; Hossein Yousefi; Neda Kargahi (Wolters Kluwer Medknow Publications, 2022)
Background: Since salivary and breast glands are both considered as a tubulo-acinar, exocrine glands, and they have a common neoplastic morphology, it is not surprising if they share a similar molecular mechanism responsible for their neoplastic transformation. From the first description of estrogen receptor-α (ER-α) in salivary tumors, tremendous attentions have been attracted to this receptor for evaluating its impact in mucoepidermoid carcinoma (MEC). Materials and Methods: In this descriptive analytics, 28 samples of MEC (14 high grade and 14 low grade) were collected from the Oral and Maxillofacial Pathology Department of Isfahan Dental School and Isfahan Alzahra Hospital. All of these samples were stained with immunohistochemical technique with ER-α marker. The expression of the receptor was evaluated by two oral and maxillofacial pathologists. Statistical data were saved at SPSS and had been analyzed by Mann-Whitney U- and independent t-tests (significance level: P ≤ 0.05). Results: The high-grade MEC was more common in patients with a higher average age (55.9); on the other hand, low-grade MEC was mostly observed in those with a mean age of 39.2 years. Moreover, high-grade MEC was more prevalent in men rather than in women. The staining intensity distribution average in high-grade MEC and low-grade MEC was 2.4 and 0.8, respectively (P = 0.48). Conclusion: The expression of ER-α in high-grade MEC was significantly more than low-grade MEC, indicating that targeting this receptor alongside surgery could bring more advantages for patients.